2015
DOI: 10.1038/srep18833
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Osteogenesis by Reduced Graphene Oxide/Hydroxyapatite Nanocomposites

Abstract: Recently, graphene-based nanomaterials, in the form of two dimensional substrates or three dimensional foams, have attracted considerable attention as bioactive scaffolds to promote the differentiation of various stem cells towards specific lineages. On the other hand, the potential advantages of using graphene-based hybrid composites directly as factors inducing cellular differentiation as well as tissue regeneration are unclear. This study examined whether nanocomposites of reduced graphene oxide (rGO) and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
117
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 224 publications
(127 citation statements)
references
References 66 publications
(71 reference statements)
9
117
0
1
Order By: Relevance
“…Calvarial defects of critical sizes were produced in rabbits and then cured with GO/β-TCP scaffold, which resulted in higher rate of naive bone formation than defects filled by unchanged β-TCP alone [126]. Similar observations were also found in the case of rGO/HAp graft which showed considerably higher (52%) bone density than HAp (26%) as well as untreated control (17%) [127].…”
Section: Graphene In Biomedical Implantationsupporting
confidence: 69%
“…Calvarial defects of critical sizes were produced in rabbits and then cured with GO/β-TCP scaffold, which resulted in higher rate of naive bone formation than defects filled by unchanged β-TCP alone [126]. Similar observations were also found in the case of rGO/HAp graft which showed considerably higher (52%) bone density than HAp (26%) as well as untreated control (17%) [127].…”
Section: Graphene In Biomedical Implantationsupporting
confidence: 69%
“…Graphene-based materials have been combined with HAP to enhance osteogenic differentiation of cells and formation of new bone [146, 149, 150]. It was reported that GO/CaCO 3 or graphene/CaCO 3 hybrid composites can enhance formation of HAP when incubated in simulated body fluid (SBF) solution [146].…”
Section: Applications In Tissue Engineering and Regenerative Medicinementioning
confidence: 99%
“…rGO sheets and HAP microparticles can adhere with each other through electrostatic interactions and hydrogen-bonding [149, 150]. The positively charged calcium moieties on the surface of HAP microparticles can be immobilized on the negatively charged hydroxyl and carboxyl groups on the surface of rGO sheets via electrostatic interactions.…”
Section: Applications In Tissue Engineering and Regenerative Medicinementioning
confidence: 99%
“…Therefore, the DCP-rGO composites could be successfully formed because of the unique structural properties of rGO sheets. In addition, the interfacial and hydrogen bond interactions between the oxygen-containing surface groups of rGO and the hydroxyl groups of DCP microparticles could also participate in the good adhesion between DCP microparticles and rGO [50,57,58]. Figure 3b showed the Raman spectra of DCP microparticles and DCP-rGO composites.…”
Section: Methodsmentioning
confidence: 99%
“…The rGO sheets were obtained by the preparation of GO using the modified Hummers and offeman method, and subsequent reduction process of GO with hydrazine hydrate (N 2 H 4 ·H 2 O) at 100 • C for 24 h [38,49,50]. The prepared rGO sheets in deionized water were sonicated for 2 h. The DCP microparticles dispersed in deionized water were physically mixed at DCP to rGO weight ratios of 2:1, 1:1, or 1:2, respectively.…”
Section: Methodsmentioning
confidence: 99%